Security and Privacy Preserving in Social Networks - Chbeir, Richard; Al Bouna, Bechara; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2013)
This volume aims at assessing the current approaches and technologies, as well as to outline the major challenges and future perspectives related to the security and privacy protection of social networks. It provides the reader with an overview of the state-of-the art techniques, studies, and approaches as well as outlining future directions in this field. A wide range of interdisciplinary contributions from various research groups ensures for a balanced and complete perspective.
Privacy in Online Social Networks -- Online Social Networks: Privacy Threats and Defenses -- Online Social Networks and Terrorism: Threats and Defenses -- User-Managed Access Control in Web Based Social Networks -- UPP+: A Flexible User Privacy Policy for Social Networking Services -- Social Semantic Network-Based Access Control -- Supporting Data Privacy in P2P Systems -- Privacy Preserving Reputation Management in Social Networks -- Security and Privacy Issues in Mobile Social Networks -- Avatar Facial Biometric Authentication Using Wavelet Local Binary Patterns -- A Flexible Image-Based Access Control Model for Social Networks -- Problems and Questions.
Keywords: Computer science; Data protection; Data encryption (Computer science).; Mass media -- Law and legislation; Computer Science; Systems and Data Security; Statistical Physics, Dynamical Systems and Complexity; Sociology, general; Media Law; Data Encryption; Information Systems Applications (incl. Internet).